Hubungan frekuensi menyikat gigi dengan karies gigi molar pertama permanen murid kelas V dan VI sekolah dasar - Warman, Anses; Arnetty, Arnetty; Ifitri, Ika; Salsabila, Selvi; Amiruddin, Amiruddin (Poltekkes Kemenkes Aceh, 2024)
Background: Caries of permanent first molar teeth is a dental hard tissue disease that often occurs in elementary school children. The cause is if you ignore oral hygiene, one of which is the frequency of brushing your teeth and improper techniques so that it can lead to dental caries.Objectives: The purpose of the study was to determine the relationship between the frequency of brushing teeth and permanent first molar caries of class grade V and VI elementary school students.Methods: The research method used is analytic with a Cross Sectional approach. The study population was all V and VI students in Nagari Tanjuang Barulak, Batipuh District, Tanah Datar Regency, totalling 143 people using saturated sampling technique and fulfilling the inclusion criteria. Data collection was carried out using permanent first molar caries examination. Data analysis used univariate and bivariate analysis with statistical tests, namely chi-square.Results: The results showed that the frequency of brushing teeth 1x a day was 51.6%, 2x a day 48.4% and ≥2 a day 0%. Students with caries were 61.3% while those free of caries were 38.7%. The test results showed a p value = 0.03 <0.05, meaning that there was a significant relationship.Conclusion: The conclusion of the study is that there is a significant relationship between the frequency of tooth brushing and permanent first molar caries in elementary school students in Nagari Tanjuang Barulak. Maternal dental health history has no association with the incidence of stunting in children.